2020
DOI: 10.1002/cncr.32992
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cost‐effectiveness of mailed fecal immunochemical testing (FIT)–based interventions for increasing colorectal cancer screening in the Medicaid population

Abstract: Background Mailed reminders to promote colorectal cancer (CRC) screening by fecal immunochemical testing (FIT) have been shown to be effective in the Medicaid population, in which screening is underused. However, little is known regarding the cost‐effectiveness of these interventions, with or without an included FIT kit. METHODS The authors conducted a cost‐effectiveness analysis of a randomized controlled trial that compared the effectiveness of a reminder + FIT intervention versus a reminder‐only interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
10
1
Order By: Relevance
“…Nevertheless, the cost per completed FIT was only slightly lower for the 2018 opt-in program versus the 2016 program. The costs of both programs were in the range of other published studies, 8,22,23 but additional research could further evaluate the costs and potential efficiencies of opt-in and opt-out mailed FIT programs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, the cost per completed FIT was only slightly lower for the 2018 opt-in program versus the 2016 program. The costs of both programs were in the range of other published studies, 8,22,23 but additional research could further evaluate the costs and potential efficiencies of opt-in and opt-out mailed FIT programs.…”
Section: Discussionmentioning
confidence: 90%
“…Though not administered by a Medicaid health plan, this study suggests that Medicaid beneficiaries are responsive to a centralized mailed FIT program and that such a program is feasible and cost-effective. 8 The study reported here fills gaps in this literature by comparing the implementation, effectiveness, and cost outcomes of 2 different mailed FIT program models implemented by a health plan with its dual-eligible Medicaid/Medicare enrollees: the first mailed FITs to enrollees due for screening, and the second delivered live calls to enrollees due for screening and mailed FITs only to those who opted to receive the mailing.…”
Section: Introductionmentioning
confidence: 99%
“…A key strength of our analysis is that we made use of a well‐established microsimulation model, replicating the French population and screening programme in a very detailed way. A previous US cost‐effectiveness analysis also showed that including a FIT kit with a reminder for CRC screening resulted in an acceptable increase in cost per person screened, compared to not including a FIT kit 37 . However, this study only considered screening costs over a 1‐year time horizon.…”
Section: Discussionmentioning
confidence: 90%
“…A previous US cost-effectiveness analysis also showed that including a FIT kit with a reminder for CRC screening resulted in an acceptable increase in cost per person screened, compared to not including a FIT kit. 37 However, this study only considered screening costs over a 1-year time horizon. We determined the costs and benefits associated with screening using two different methods of invitation over a lifetime.…”
Section: Us Treatment Costsmentioning
confidence: 99%
“…In this issue of Cancer , Wheeler and colleagues report the cost effectiveness of a mailed FIT program delivered to 2144 Medicaid beneficiaries by a public health department in North Carolina 10 . Beneficiaries were randomized to receive mailed screening reminders and an FIT kit (with a postage‐paid return envelope) or mailed reminders with no FIT kit, but with a phone number to request a mailed kit and the address of a laboratory facility where it could be picked up in person.…”
Section: Figurementioning
confidence: 99%